GRAIN STORAGE DEFICIT IN BRAZIL (REMUNOM, 2024)
In the ranking of the countries that produce the most grains, Brazil is among the five largest food producers in the world and has been surpassing the production index with each harvest, combining new technologies with agricultural activities and playing a crucial role for the economy. It stands out for its grain production of rice, beans, wheat, cotton, soybeans and corn, with a considerable increase in the last two. Given the high returns behind the impressive numbers of record harvests and considerable exports, there is a critical challenge affecting the stability and sustainable growth of this industry: the grain storage deficit. This problem goes far beyond logistics; it directly impacts food security, the economy and the country's competitiveness in global markets. The lack of adequate spaces to store grain safely and efficiently has profound impacts on the entire production chain, from farmers dealing with post-harvest losses to exports facing administrative challenges. Despite all the strategies that have been put in place, static storage capacity has not kept pace with the growth in Brazilian production, and the high level of grain wastage and poor distribution of warehouses contributes to significant losses.